Narcolepsy With or Without Cataplexy In The Pediatric Population: A Systematic Review - Nazir, Racha; S Bennett, David; Sedky, Karim (Journal of Sleep And Sleep Disorder Research, 2018)
Study Objectives: Narcolepsy diagnosis has been associated with a long lag time between the onset of the disorder and the diagnosis itself among patients with the disorder. This article reviews the childhood epidemiology of idiopathic narcolepsy, including its prevalence, subtypes, and disease progression. Methods: A literature review was conducted to include both published and unpublished data on pediatric narcolepsy. All English language articles were included through April, 2015. Results: Time from symptom onset to diagnosis for children is approximately three years. The prevalence of cataplexy appears to be lower in children compared to adults, suggesting a later onset of cataplexy. The presence of cataplexy, however, was unrelated to demographic factors and laboratory findings. Conclusion: There is a substantial lag-time between initial symptom presentation and diagnosis in children with narcolepsy. A less quintessential presentation of narcolepsy might occur in children relative to adults, making diagnosis more challenging. Continued improvements in narcolepsy education for both pediatricians and parents might facilitate earlier identification and diagnosis of the disease, thus leading to improved outcome.
Keywords: Narcolepsy; pediatric narcolepsy; cataplexy; narcolepsy in children